2019
DOI: 10.1007/s00262-019-02448-z
|View full text |Cite
|
Sign up to set email alerts
|

Personalized neoantigen-pulsed dendritic cell vaccines show superior immunogenicity to neoantigen-adjuvant vaccines in mouse tumor models

Abstract: Development of personalized cancer vaccines based on neoantigens has become a new direction in cancer immunotherapy. Two forms of cancer vaccines have been widely studied: tumor-associated antigen (including proteins, peptides, or tumor lysates)-pulsed dendritic cell (DC) vaccines and protein-or peptide-adjuvant vaccines. However, different immune modalities may produce different therapeutic effects and immune responses when the same antigen is used. Therefore, it is necessary to choose a more effective neoant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“… 23 , 24 Some studies reported that antigen-loaded DC vaccines induced stronger immune responses than vaccines composed of antigens and adjuvants. 25 , 26 Therefore, neoantigen-based DC vaccines for cancer treatment seem to be promising and have been extensively investigated. 24 To date, neoantigen-based DC vaccines have shown clinical success in melanoma and other solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“… 23 , 24 Some studies reported that antigen-loaded DC vaccines induced stronger immune responses than vaccines composed of antigens and adjuvants. 25 , 26 Therefore, neoantigen-based DC vaccines for cancer treatment seem to be promising and have been extensively investigated. 24 To date, neoantigen-based DC vaccines have shown clinical success in melanoma and other solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Neoantigens can be identified and selected using whole exome sequencing of tumor and blood cell DNA and bioinformatics algorithms. In a murine lung carcinoma model, neoantigen-pulsed DC vaccines were superior to neoantigen-adjuvant vaccines in activating immune responses and inhibiting tumor growth ( 101 ). A first demonstration of this approach in human subjects was provided in a phase 1 trial in metastatic melanoma, showing a remarkable induction of de novo T cell responses after vaccination with personalized tumor neoantigen-loaded DCs.…”
Section: The Way Forwardmentioning
confidence: 99%
“…Same promising results were achieved in ovarian cancer patients by intranodal injection of neopeptide-loaded DC vaccine [ 36 ]. Interestingly, a recent study published by Zhang et al demonstrated that a personalized neoantigen-pulsed DC vaccine has superior immunogenicity to neoantigen-adjuvant vaccine in murine tumor models [ 37 ].…”
Section: Tumor-specific Antigensmentioning
confidence: 99%